CHEMISTRY TEACHING BY MEANS OF ICT-BASED RESOURCES WITH THE REGARD FOR PREFERRED LEARNING STYLES OF UNIVERSITY STUDENTS (Journal of Information Technologies in Education (ITE), 2013)
Expediency and effectiveness of the use of various ICT-based learning resources in teaching of basic chemistry disciplines was studied. Preferred learning styles of 46 graduate students were assessed by the Felder-Soloman Index of Learning Styles. More than a half of 45 considered resources were found to be dependent on students’ preferred learning style. Certain corrections in the use of style-dependent resources are necessary to improve conformity with students’ learning preferences.
Keywords: ICT-based learning resources; university chemistry teaching; Felder-Soloman preferred learning style